2011
DOI: 10.2190/tw.41.3.f
|View full text |Cite
|
Sign up to set email alerts
|

Emphasizing Research (Further) in Undergraduate Technical Communication Curricula: Involving Undergraduate Students with an Academic Journal's Publication and Management

Abstract: This article presents follow-up information to a previous publication regarding ways to increase emphasis on research skills in undergraduate Technical Communication curricula. We detail the ways our undergraduate program highlights research by requiring majors to complete senior thesis projects that culminate in submission to an online peer-reviewed journal housed at our institution. This article also describes the roles our undergraduate students play in helping to manage the publication of that academic jou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…An example of empirical research using interviews can be found in Taylor’s (2011) study of how students interpret instructor feedback. As an example of a textually based study, we consider Ford and Newmark’s (2011), which involves considerations of how to incorporate an emphasis on research through their examination of students’ work on an undergraduate writing journal.…”
Section: Rq2: Can We Categorize the Types Of Research Being Done To Smentioning
confidence: 99%
“…An example of empirical research using interviews can be found in Taylor’s (2011) study of how students interpret instructor feedback. As an example of a textually based study, we consider Ford and Newmark’s (2011), which involves considerations of how to incorporate an emphasis on research through their examination of students’ work on an undergraduate writing journal.…”
Section: Rq2: Can We Categorize the Types Of Research Being Done To Smentioning
confidence: 99%
“…hese initiatives are undertaking by the following stages: a) literature review and research about a speciic topic of the ield; b) oral presentations for department staf and guests (practitioners); c) conference presentations; and, d) journal submissions. hese initiatives also advocate for journal internships in which students learn how to write to be published and how to manage the publishing backstage (i.e., the administrative side of communicating with reviewers and authors, as well as the technical side of journal production by web design, content management, website updating, and e-journal promotion) (Ford & Newmark, 2011).…”
Section: Subject Matter Of the Courses: Science Communication Profesmentioning
confidence: 99%
“…he U.S. scholarship of teaching on science communication and research skills (Ford & Newmark, 2011) might be further explored in the Latin-American case by contextualizing what counts as scientiic knowledge production and to what extent this is related to higher education in general and to Engineering majors in particular. hese particular U.S. experiences for teaching genre practices that merge scientiic and professional audiences (e.g., literature reviews or oral presentations that are addressing simultaneously academic and industry audiences) (Ford & Newmark, 2011) continue nourishing conversations about the rhetorical nature of science and technology (science as argument) (Miller, 2004). In this regard, it is interesting to mention that in the Latin-American case, two pedagogically-oriented publications mentioned as limitation that students struggle in developing audience awareness (López & Ramírez, 2012;; this diiculty might be also associated with assigning writing activities that are exclusively addressing instructors (writing to learn).…”
Section: Subject Matter Of the Coursesmentioning
confidence: 99%
“…Previous studies have shown that the instructors have tried different strategies (Ball et al, 2020) to enhance the research experience of undergraduate students by designing suitable research assignments as a course project. Moreover, a survey of old literature reveals that the undergraduate research activities undertaken are through summer internship projects (Houser & Lemmons, 2018), course project/term projects (Amekudzi et al, 2010;Ford & Newmark, 2011;Ponce et al, 2021), or some kind of special research program organized involving undergraduate students. For example, the study reported by (Morley et al, 1998) is an evaluation of junior-level undergraduate students mentored by a graduate student during an eight-week program summer internship program.…”
Section: Introductionmentioning
confidence: 99%